[Et3NH][HSO4]-mediated functionalization of hippuric acid: an unprecedented approach to 4-arylidene-2-phenyl-5(4H)-oxazolones1. Issue 65 (16th July 2015) - Parveen, Mehtab; Ahmad, Faheem; Malla, Ali Mohammed; Azaz, Shaista; Silva, Manuela Ramos; Silva, P. S. Pereira
<x xml:space="preserve">Abstract</x> Facile, sustainable and economical synthesis of Erlenmeyer azlactones.